KESIAPAN BELAJAR SISWA DAN INTERAKSI BELAJAR MENGAJAR TERHADAP PRESTASI BELAJAR - Darso, Darso (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2011)
One of the most important parts to improve the ability to read drawings in learning process is students' learning readiness and teaching-learning interaction on a subject of reading technical drawings, which are often overlooked by school. This study aims to investigate the influence of students' learning readiness and teaching-learning interaction on achievement in the subject of reading technical drawings. The study shows that there is a correlation between students’ learning readiness and their academic achievement, which is 0,45; the correlation between teaching-learning interactions exists in the level of 0,67; there is a correlation between students’ learning readiness and teaching-learning interactions in the level of 0,34; and there is a correlation of students’ learning readiness and teaching-learning interaction on academic achievement, which is 0,71. The coefficient for the variable of students’ readiness and teaching-learning interaction is significant in the level of significance α = 0.05. Thus, it can be concluded that the students' learning readiness and teaching-learning interactions between teachers and students provide a meaningful/significant impact on the academic achievement in reading technical drawings subject